ANALISIS PENGARUH PMDN DAN PMA TERHADAP PDB DI INDONESIA DALAM PERSPEKTIF EKONOMI ISLAM - Dewi, Shafira Visca; Bahtiar, Muhammad Yusuf; Taufiqurrahman, Taufiqurrahman (Journal of Information System, Applied, Management, Accounting and Research, 2024)
Gross Domestic Product is the total number of products in the form of goods and services produced by production units within a country's territorial borders (domestic) for one year or is often also interpreted as the total market value of all final services produced by a country or society during one period. a certain time, for example one year. GDP will calculate the production of goods and services produced by foreign companies/persons operating in the territory of the country concerned. The source of GDP revenue in Indonesia is influenced by investment factors, both from PMDN and PMA on Gross Domestic Product (GDP). The type of research used is quantitative. The method used in this research is the Error Correction Model (ECM). The data used is secondary data published by the Ministry of Finance with time series data in the year of observation, namely 2002-2023 in Indonesia. The test was carried out with the help of the Eviews 10 software application. The results of this research show that only the Domestic Investment variable has a significant effect on Gross Domestic Product, while the Foreign Investment variable has no significant effect on Gross Domestic Product.